Relationship of shift work with liver enzyme abnormalities and nonalcoholic fatty liver disease: A retrospective cohort study of Thai workers in Bangkok, Thailand: 10.55131/jphd/2024/220110 - Taechasan, Napas; Jiamjarasrangsi, Wiroj (Journal of Public Health and Development, 2024)
Shift work, particularly night shift work, has several detrimental health outcomes. This retrospective study investigated the associations of shift work with the incidence rates of liver enzyme abnormalities and nonalcoholic fatty liver disease (NAFLD) using the annual health check-up database between 2009 and 2016 and self-administered questionnaires from two large organizations in Thailand. Among 10,205 participants, 3620 eligible participants, classified into three subgroups by their shift work status, were followed up until abnormal liver outcomes were observed. The incidence rate of abnormal outcomes was calculated, and Cox proportional hazard models were used to assess the associations. Current shift work was not associated with abnormal liver outcomes, including elevated alanine aminotransferase and aspartate aminotransferase levels, elevated lipid accumulation product (e-LAP), and elevated hepatic steatosis index (e-HSI). However, when the frequencies and duration of shift work were investigated, the duration of shift work was associated with NAFLD outcomes. Healthcare personnel with 10–20 years of shift work experience had a higher risk of e-LAP (adjusted hazard ratio [HR] = 1.31, 95% confidence interval [CI] = 1.04–1.65), while workers with more than 20 years of shift work had a lower risk of e-LAP (adjusted HR = 0.77, 95% CI–0.62–0.97). Nonhealthcare shift workers with fewer than 10 years of work exposure had a higher risk of e-HSI (adjusted HR = 4.30, 95% CI = 1.28–14.47). In summary, the shift work status was not associated with liver abnormalities, but the duration of shift work was associated with NAFLD.